Integrating local knowledge and biophysical modeling to assess nitrate losses from cropping systems in drinking water protection areas. (July 2015) - Dupas, Rémi; Parnaudeau, Virginie; Reau, Raymond; Jeuffroy, Marie-Hélène; Durand, Patrick; Gascuel-Odoux, Chantal
Abstract: Addressing the issue of agricultural pollution in water protection areas (WPA) requires assessing the impact of agricultural activities at regional scales. However, current water quality modeling studies often neglect the agronomic concept of a cropping system and interactions with soils. This paper presents a participatory assessment framework involving local experts in building a shared diagnosis of nitrate losses from cropping systems in a WPA. It includes a co-designed typology of landscape units and participatory assessment of nitrate losses with the modeling software Syst'N. Results show that characteristics of cropping systems depended on soils and that nitrate losses were highest in shallow soils. Intercrop periods were identified as critical periods for nitrate leaching, which demonstrates the importance of considering pluri-annual crop rotations rather than individual crops. The framework is generic for a modeling approach based on the involvement of local experts, who define their functional system in an agronomically sound way. Highlights: Participatory assessment of nitrate losses from cropping systems at a regional scale. User-friendly agronomic modeling software to facilitate discussion with participants. Characteristics of cropping systems depend on soil types. Predicted nitrate losses result from interactions between cropping systems and soils.